Shaking table test on a low-damage controlled multiple-rocking-column steel frame. (1st March 2022) - Xiang, Ping; Song, Guanqing; Fan, Kui; Li, Zhuofeng; Jia, Liang-Jiu
Highlights: A low-damage controlled multiple-rocking-column steel frame system with friction connections proposed. 1/3 scaled shaking table tests of a three-story multiple-rocking-column steel frame conducted. Excellent self-centering capacity contributed mainly by the gravity load. The main structural members stayed elastic with low damage even under the MCE level excitation. A preliminary design procedure to achieve the multiple rocking mechanism proposed. Abstract: Ancient timber structures represented by the Shaka Pagoda can remain intact after strong seismic actions. Inspired by the rocking and energy dissipation mechanisms of ancient timber structures, a multiple-rocking-column steel frame (MRCSF) system was proposed in this study. The proposed system consists of continuous beams, segmented columns and self-centering friction connections. Friction joints are employed at the beam-column and column base connections to dissipate energy, and the self-centering capacity is mainly provided by the gravity load and additional springs at the connections. A 1/3-scale model of a three-story MRCSF was designed, fabricated and tested on a shaking table at Tongji University. Test results showed that the columns started to rock when subjected to excitations beyond the frequent earthquake level, as expected. The tested frame successfully underwent a series of strong excitations and exhibited excellent low-damage characteristics. Negligible residual drifts and structural damage were measured after the tests. Finally, a feasible design process for the newly proposed MRCSF system was proposed.